Uji In Silico Ellagic Acid sebagai Agen Anti Hiperpimentasi: Uji In Silico Ellagic Acid sebagai Agen Anti Hiperpimentasi - Ni Kadek Sita Febriyanti (Jurnal Jejaring Matematika dan Sains, 2022)
Hyperpigmentation is a skin problem that occurs due to excess melanin synthesis. One of the factors that cause hyperpigmentation is continuous exposure to UV rays on the skin. Melanin biosynthesis is catalyzed by the melanogenic enzyme tyrosinase. Melanin synthesis can be inhibited by using anti hyperpigmentation agents, one of which is sourced from natural ingredients. Ellagic acid is a phenolic compound that is widely found in plants and has antioxidant activity so that it can inhibit hyperpigmentation through ROS inhibition mechanism. This study aims to determine the potential of ellagic acid in inhibiting the tyrosinase enzyme which will be compared with its native ligand in silico. The in silico test was carried out by molecular docking with the steps of preparation and optimization of ellagic acid using Hyperchem 8, preparation of the tyrosinase enzyme using Chimera 1.11.1, validation and docking using AutoDockTools 1.5.6 equipped with Autodock 4 and Autogrid 4. Molecular docking methods can be declared valid if the value of RMSD (root mean square distance) obtained is not more than 3 . The results of the molecular docking test showed that ellagic acid had an affinity for the tyrosinase enzyme. The bond energy values ​​obtained indicate that the affinity of ellagic acid is stronger and more stable for tyrosinase compared to native ligands. The bond energy value between ellagic acid and tyrosinase is -5.78 kcal/mol. Meanwhile, the binding energy between tyrosinase and its native ligand is -4.83 kcal/mol, so that ellagic acid has the potential as an anti hyperpigmentation agent through the mechanism of inhibition of tyrosinase enzyme activity.